Polysaccharide Specific Monoclonal Antibodies Provide Passive Protection against Intranasal Challenge with Burkholderia pseudomallei - AuCoin, David P.; Reed, Dana E.; Marlenee, Nicole L.; Bowen, Richard A.; Thorkildson, Peter; Judy, Barbara M.; Torres, Alfredo G.; Kozel, Thomas R. (PLOS ONE, 2012)
Burkholderia pseudomallei is a Gram-negative bacillus that is the causative agent of melioidosis. The bacterium is inherently resistant to many antibiotics and mortality rates remain high in endemic areas. The lipopolysaccharide (LPS) and capsular polysaccharide (CPS) are two surface-associated antigens that contribute to pathogenesis. We previously developed two monoclonal antibodies (mAbs) specific to the CPS and LPS; the CPS mAb was shown to identify antigen in serum and urine from melioidosis patients. The goal of this study was to determine if passive immunization with CPS and LPS mAbs alone and in combination would protect mice from a lethal challenge with B. pseudomallei. Intranasal (i.n.) challenge experiments were performed with B. pseudomallei strains 1026b and K96423. Both mAbs provided significant protection when administered alone. A combination of mAbs was protective when low doses were administered. In addition, combination therapy provided a significant reduction in spleen colony forming units (cfu) compared to results when either the CPS or LPS mAbs were administered alone.